Treatment of jaw deformity with temporomandibuilar disorders nsing operation of mandibular spliting mothod and arthroscopic disc suturing technique - FUZITA, Yukihiro; SOMA, Kunimichi; KASAI, Takashi; OHTSUKI, Kayoko; OHNISHI, Mastoshi (Journal of the Japanese Society for the Temporomandibular Joint, 1994)
Arthroscopic surgery is accepted as a type of temporomandibular joint (TMJ) arthroscopy and is used for the treatment of lesions confined to a joint cavity. As a new treatment for mandibular deformity accompainied by an internal derangement of the TMJ frequently occurring in the clinical setting, we evaluated a surgical procedure combining arthroscopic disk suturing-fixation technique and sagittal spliting of the mandibular ramus as the treatment of mandibular deformity. The subjects were ten patients with mandibular deformities in whom longstanding TMJ symptoms had been confirmed before surgical operation, and who had been diagnosed as having TMJ internal derangement with disk displacement. The diagnosis was done using CT double contrast of TMJ or MRI. The surgical procedure consisted of the following steps: (1) Prior to the conventional occlusal improvement by sagittal splitting of the mandible, disk displacement was corrected and the disk thickness was increased by disk traction and fixation to the posterior wall and articular fossa of the upper joint cavity by arthroscopic laser surgery and suturing technique. (2) After sagittal splitting of the ramus, the mandibular head of the outer bone fragment was fitted to the lower surface of the disk whose position had been corrected and then fixed to the mandibular body with titanium screws or mini-plate system. (3) Clinical results were excellent, and long standing TMJ symptoms subsided in eight cases and markedly improved in two cases after operation.